Thyroid Functioning and Fatigue in Women With Functional Somatic Syndromes – Role of Early Life Adversity - Fischer, Susanne; Markert, Charlotte; Strahler, Jana; Doerr, Johanna M.; Skoluda, Nadine; Kappert, Mattes; Nater, Urs M. (Frontiers in Physiology, 2018)
Objective Fatigue is a core feature of functional somatic syndromes (FSS). Fatigue is also prominent in patients with thyroid diseases, which is unsurprising given the role of the hypothalamic-pituitary-thyroid (HPT) axis in regulating physiological energy demands. Research in healthy women has shown that early life adversity is linked with alterations in the HPT axis. In view of the substantial prevalence of early life adversity in patients with FSS, our aim was to investigate whether HPT functioning is related to a) fatigue, and b) early life adversity in these patients. Methods N=33 female patients with FSS and n=30 age-matched controls were recruited. Fasting morning blood samples were taken to determine thyroid-stimulating hormone (TSH), free triiodothyronine (fT3), and thyroxine (fT4). General, physical, and mental fatigue were measured via the Multidimensional Fatigue Inventory. Early life adversity was measured using the Childhood Trauma Questionnaire. Results Patients with FSS did not differ from controls in any thyroid parameters (all p>.672). However, the lower the patients' TSH and the higher their fT4, the greater was their general (Beta=-0.32, p=.064; Beta=0.35, p=.038) and physical (Beta=-0.47, p=.007; Beta=0.32, p=.077) fatigue. In addition, emotional neglect (Beta=-0.32, p=.057), physical neglect (Beta=-0.60, p=.001), physical abuse (Beta=-0.47, p=.015), and sexual abuse (Beta=-0.40, p=.026) were linked with lower TSH. Conclusions The lower the TSH and the higher fT4, the more fatigue was reported by patients with FSS. In addition, lower TSH was linked with more early life adversity. Larger, prospective studies are warranted to determine whether HPT functioning may be a mediating pathway between early life adversity and fatigue in FSS.